If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4w + -13w = 54 Combine like terms: 4w + -13w = -9w -9w = 54 Solving -9w = 54 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Divide each side by '-9'. w = -6 Simplifying w = -6
| 2x^2-540=0 | | c-8/-2=11-4c/11 | | 3x=4(5x+2) | | -24=6x+3x+3 | | 3x+y+z=37 | | (12N-N)+5= | | 13x+13=60 | | -8x-2+4x+7=31 | | x-8/6+2=4 | | -10.3m=-10.6m-3.21 | | 3+6x+7x=42 | | -10.3m=-10.6-3.21 | | I=0.8rt | | -16=-6x-2x-8 | | 1.2x-0.8=0.8x+2 | | 5-x=3(x-11) | | 1.2x-0.8=0.8+2 | | 5.6m+7.8-5.7m=-4.1-0.1m+11.9 | | x(3.4)-8=32.8 | | 46=3x+6x-8 | | 4n+2=10n-16 | | -14.6g=-13.4g+12.12 | | y-20=4x | | 2x=-x-2 | | R+6/5=r+8/7 | | 4-5x+6x=-4 | | 3x/5-6/15=x/3+2/5 | | 3y+6+2y=-24 | | 6x/7(10-10)=10x+2 | | J=20(c-100) | | -29r=42 | | -10-7w-3w=-15w+20 |